[Translated article] Folliculotropic Mycosis Fungoides in a Latin American Hospital: Survival Analysis - H.C. Pérez; S. Morales; L. Enciso; J.A. Carreño; X. Rueda (Actas Dermo-Sifiliográficas, 2022)
Introduction: Folliculotropic mycosis fungoides is a variant that has poor prognosis and a variable clinical presentation. Concerns have been expressed that the current TNMB staging of this tumor may not be useful. A recently developed classification system based on clinical and histologic variables classifies this tumor as early or advanced, a distinction found to correlate with prognosis. The aim of this study was to compare survival in FMF in Colombia between patients with early versus advanced tumors. Material and methods: Retrospective, observational study of clinical course and outcomes in patients with FMF treated at the National Cancer Institute of Colombia between 2008 and 2020. Survival was compared between early and advanced disease. Results: Twenty-one patients (11 with early FMF and 10 with advanced FMF) were studied. Seven patients, all with advanced disease, died. Survival at 5 years was 62% overall and 40% for patients with advanced FMF. No differences were observed when survival was analyzed according to TNMB stage. Conclusions: TNMB staging is not useful in FMF. The new classification system based on clinicopathologic features appears to provide reliable information for assessing prognosis and guiding treatment decisions. Resumen: Introducción: La micosis fungoide foliculotropa es una variante de mal pronóstico y presentación clínica variada. Se ha planteado que la estadificación TNMB usada para esta neoplasia no es útil. En una propuesta reciente basada en aspectos clínicos e histológicos, se clasifica en enfermedad temprana y avanzada, encontrando diferencias pronósticas entre las dos categorías. El objetivo de este estudio fue comparar la supervivencia de estos dos grupos en nuestra población. Materiales y métodos: Se realizó un estudio observacional retrospectivo de serie de casos donde se evaluó la evolución clínica de los pacientes con micosis fungoide foliculotropa tratados en el Instituto Nacional de Cancerología entre el 2008 y el 2020, realizando un análisis comparativo de supervivencia entre aquellos que tienen enfermedad temprana y enfermedad avanzada. Resultados: Se incluyó a un total de 21 pacientes, 11 de los cuales presentaban enfermedad temprana y 10 enfermedad avanzada. Se identificaron siete decesos, todos ellos en los pacientes con enfermedad avanzada. La supervivencia global de la población total a cinco años fue del 62%, mientras que para la población con enfermedad avanzada fue del 40%. No hubo diferencias en la supervivencia según la estadificación TNMB. Conclusión: La estadificación TNMB no es útil para los pacientes con una micosis fungoide foliculotropa. Por el contrario, la nueva clasificación clínico-patológica parece brindar información pronóstica fiable y permite tomar medidas terapéuticas acordes.